Silver nanoparticles/graphene oxide decorated carbon fiber synergistic reinforcement in epoxy-based composites - Wang, Caifeng; Zhao, Min; Li, Jun; Yu, Jiali; Sun, Shaofan; Ge, Shengsong; Guo, Xingkui; Xie, Fei; Jiang, Bo; Wujcik, Evan K.; Huang, Yudong; Wang, Ning; et al. (Polymer (Guilford), 2017)
A novel two-layer reinforced carbon fiber (CF), i.e., Ag nanoparticles (Ag NPs)/graphene oxide (GO) reinforced CF (named as CF/Ag/GO) was prepared by an electrochemical deposition and electrophoretic deposition (EPD) consequently. The modified fiber showed an increased interfacial shear strength (IFSS) and tensile strength. Transmission electron microscopy (TEM), scanning electron microscopy (SEM), Fourier transform infrared spectra (FTIR), X-ray photoelectron spectroscopy (XPS), Raman spectrometer, atomic force microscopic (AFM) and dynamic contact angle analysis (DCA) were carried out to investigate CF reinforced composites. And test results demonstrated that the presence of Ag NPs and GO sheets increased the surface roughness and surface energy of CFs significantly. IFSS of CF/epoxy and the tensile strength of CFs were increased by 86.1% and 36.8%, respectively. Ag NPs filled in the cracks in CF effectively to enhance the tensile strength, while GO sheets improved the wettability of resin on CFs and formed mechanical interlocking between CFs and epoxy resin. These Ag NPs and GO sheets worked together in a ferocious synergy on the interface of CF and epoxy to cause the enhanced mechanical properties. [Display omitted] •Electrodeposition was efficient to introduce Ag nanoparticles on carbon fiber.•Electrophoretic deposition was efficient to introduce GO sheets on carbon fiber.•Ag NPs filled surface cracks and enhanced the tensile strength of CF by 36.8%.•GO sheets deposited on Ag-carbon fiber surface increased fiber surface wettability.•IFSS of carbon fiber/epoxy composites was increased by 86.1%.